Clock gene polygenic risk score and seasonality in major depressive disorder and bipolar disorder. (26th July 2020) - Ferrer, Alex; Costas, Javier; Gratacos, Mònica; Martínez‐Amorós, Èrika; Labad, Javier; Soriano‐Mas, Carles; Palao, Diego; Menchón, Jose Manuel; Crespo, Jose Manuel; Urretavizcaya, Mikel; Soria, Virginia
Abstract: Seasonal changes in mood and diurnal preference are two well‐characterized chronobiological phenotypes in major depressive disorder (MDD) and bipolar disorder (BD). The biological mechanisms regulating physiological changes related to seasonality and chronotype involve several genes known as "clock" or circadian genes. Our goal was to study the relationship between the polygenic risk score (PRS) obtained from a set of clock genes and chronobiological traits in patients with mood disorders. The sample included 445 patients with mood disorders (256 MDD; 189 BD). Seasonality was assessed using the Seasonal Pattern Assessment Questionnaire (SPAQ), and chronotype was assessed using the Horne and Östberg Morningness–Eveningness Questionnaire. We selected 248 single nucleotide polymorphisms located within 19 genes. PRS for both MDD and BD was calculated using the Psychiatric Genetics Consortium latest datasets as discovery samples. Another PRS was calculated using results from a genome‐wide association study focusing on chronotype. SPAQ results were significantly associated with MDD‐PRS ( p = 0.037) and chronotype‐PRS ( p = 0.019), which also showed a significant interaction with age ( p = 0.039). No significant association was observed between the measured PRS and chronotype. Our results reflect that small effect variants associated with MDD and chronotype within clock genes are associated with seasonality traits in patients with mood disorders, further explaining the mechanism through which the circadian system might influence mood disorder clinical presentation. Future studies measuring PRS from specific gene sets and focusing on biological endophenotypes will help to elucidate the pathways from genetic variations to clinical outcome. Abstract : Our main finding is a significant association between higher PRS in clock genes and higher seasonality using the major depressive disorder discovery sample.